Utilization of sugar cane by-product and biological agents to improve the quality of rice - Oktavia Sarhesti Padmini; Sri Wuryani; Rukmowati Brotodjojo (Jurnal Agrivet, 2014)
The purpose of this study was to examine the effect of boiler ash which is a waste of sugar industry and liquid organic fertilizer (LOF) to improve the quality of rice. Experiments were set up using split plot and arranged in completely randomized design, with three replicates. Main plots were composed of inorganic fertilizers on 2 levels, namely: 100% farmer’s dose and 50% farmer’s dose plus boiler ash 10 tons/ha. Sub plots was spraying frequency of LOF "Bacteria" and LOF "Plus" with concentration of 15 mL /L consists of five levels, namely: 2, 3, 4, 5, 6 times spraying. The results showed the use of boiler ash can improve the quality of rice. Semi-organic farming system with the addition of boiler ash and spraying the mixture of LOF "Bacteria + LOF “Plus" and LOF "Bacteria" four and five times increase the yield and quality of healthy rice including calcium content and amylopectin.